Lean Healthcare applied toward turning a Pharmacy Service Patient Centered - Zanotto, Bruna Stella; Bittencourt, Gabriela C.; Tortato, Caroline; Martinbiancho, Jacqueline K.; Chagas, Janaína R.; Ruschel, Karen Brasil; Etges, Ana Paula; Polanczyk, Carisi A. (VITTALLE - Revista de Ciências da Saúde, 2020)
Introduction. Pharmaceutical service optimization requires a comprehensive understanding of resource usage. The aim of the study is to analyze how Lean Healthcare principles can contribute toward turning a pharmacy service patient-centered and value oriented.Methods. Understand how clinical pharmacists’ resources are effectively used by patients in an academic hospital using lean tools, such as value stream mapping and activity designation matrix, determine the amount of time each professional is involved in specific activities, and identify activities that add value. The data were mainly obtained through interviews with professionals, time-motion observational studies, chronoanalysis and meetings with the head of the unit.Results. A process flow map is designed for clinical pharmacy services, and it considers the relationship between the activities and their added value base. An exploration of the map shows that the activity “clinical rounds” is the most time consuming (27%) and not necessarily considered value-added by both parties (pharmacists staff and head of service). It is notable the opportunity the service has to prioritize the high-risk patients and to make a good time management; furthermore, activities that are of high value to patients are being performed and monitored by interns. Conclusions. The role of pharmacists should evolve from now on to be congruent with the new realities of healthcare. When value is questioned, we are encouraged to reflect on the activities engaged in by professional pharmacists in a clinical/surgical unit of a hospital. Through these tools, we could infer how the system is engaged and how it can be transformed toward added value.